2014
DOI: 10.4172/2155-9619.1000166
|View full text |Cite
|
Sign up to set email alerts
|

The Predictive Value of Pretreatment 18-F-FDG-PET-CT in Locally Advanced Nasopharyngeal Cancer Patients Treated Definitively with Induction Chemotherapy Followed by Concurrent Chemo-Radiotherapy

Abstract: AimsThis study aimed to evaluate the role of pretreatment 18F-Fluorodeoxyglucose positron emission tomography (18F-FDG-PET-CT) as a predictor of disease-free survival (DFS), and overall survival (OS) in locally advanced nasopharyngeal carcinoma (LANPC) patients treated definitively with docetaxel-based induction chemotherapy followed by concurrent chemoradiation (CRT).Materials and methodsThis is a retrospective study approved by the institutional review board and included LANC patients treated definitively an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Moreover, the final result of our trim and fill sensitivity analysis was not affected after incorporating the hypothetical missing literatures, which demonstrates that our analysis was reliable. In addition, the included studies of this meta-analysis are almost in Asia, only one [ 41 ] in Africa, none in Europe and other continents. Because the incident of NPC is high in these regions and countries and it may cause the bias of the race of humans.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the final result of our trim and fill sensitivity analysis was not affected after incorporating the hypothetical missing literatures, which demonstrates that our analysis was reliable. In addition, the included studies of this meta-analysis are almost in Asia, only one [ 41 ] in Africa, none in Europe and other continents. Because the incident of NPC is high in these regions and countries and it may cause the bias of the race of humans.…”
Section: Discussionmentioning
confidence: 99%
“…and Lee et al. found agreement that high 18 F‐FDG uptake, indicated by a cutoff SUV max of ≥8, may indicate a poor outcome in newly diagnosed patients with locally advanced NPC receiving chemotherapy and radiotherapy 35,38 . In a more recent study by Zhang et al., SUV‐Tumor and SUV‐Nodal were identified as independent predictors for distant metastases‐free survival (DMFS) 39 …”
Section: Discussionmentioning
confidence: 93%
“…Several investigators suggested SUV would be valuable in prognosis, 23,[34][35][36][37] while other studies revealed its uselessness. 17 35,38 In a more recent study by Zhang et al, SUV-Tumor and SUV-Nodal were identified as independent predictors for distant metastases-free survival (DMFS). 39 Recently, researchers revealed that MTV and TLG were superior to SUV alone in predicting prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Among the 15 studies on FDG-PET included in the current review, most evaluated the maximum SUV (SUV max ), either alone (n = 11) ( 100 103 , 105 108 , 110 , 112 , 113 ); some also proposed other metabolic parameters, such as metabolic tumor volume (MTV; n = 1) ( 99 ) or TLG (n = 2) ( 104 , 111 ) ( Supplementary Table 6 ). A single study further evaluated the difference in prognosis between PET-CT-guided dose-painting intensity-modulated radiation therapy (IMRT) and CT-based IMRT ( 109 ).…”
Section: Discussionmentioning
confidence: 99%